Improvement in Cyclic Stability of Sodium Ion Battery Cathodes through Surface Modification - Moeez, Abdul (My University, 2021)
Layered type cathodes used in Sodium Ion batteries are prone to structural degradation as they undergo electrochemical cycling. The structural degradation is the consequence of transition metal dissolution due to unstable or non-uniform cathode-electrolyte interface (CEI), formation of side products like Hydrofluoric acid, formation of new phases in the cathode structure, moisture and carbon dioxide ingression or Jahn-Teller distortion. Some of the approaches used in past employed metal-oxide coatings, electrolyte engineering, replacement of transition metal ions and doping of different elements. However, these strategies were limited to low capacity cathodes. The structural degradation is more prominent in high capacity cathodes like Na0.55[Ni0.1Fe0.1Mn0.8]O2 (NFM) as larger number of Na ions are de-intercalated. Improvement in the cyclic stability of these cathodes remains a challenge. In this thesis, a fluoride based coating has been employed over the cathode particles to prevent the dissolution of transition metals in Localized Highly Concentrated Electrolyte (LHCE) thus maintaining the structural integrity of cathode over longer cycling life. This procedure resulted in capacity retention of 92% over 100 cycles at 0.1C for coated cathode as compared to 76.9% for uncoated cathode. Moreover, X-ray Diffraction (XRD) and Angle Resolved X- ray Photoelectron Spectroscopy (AXPS), revealed that the fluoride coating has been integral in achieving uniform and robust cathode electrolyte interface thus preventing the transition metal dissolution.
Thesis (Master's)--University of Washington, 2021
Keywords: Cathode; Coating; High Capacity; Sodium Ion; Surface Modification; Materials Science; Energy; Materials science and engineering